Motoric and sensory play as an English teaching method to teach pre-school student’s vocabulary - Nita Aprilia Utami; Mulyadi Mulyadi (University of Muhammadiyah Malang, 2025)
This study discusses the contribution of using motoric and sensory play to activeness and vocabulary mastery. The scope of this study focuses on motor and sensory play methods for teaching vocabulary in early childhood students. The purpose of this study is to find out the students' participation in the use of motor and sensory play method in vocabulary learning at AL-Uswah English Class (AEC) Pamekasan, and to find out whether motor and sensory play supports the exploration of vocabulary mastery at AL-Uswah English Class (AEC) Pamekasan from the perspective of teachers and students of AL-Uswah English Class (AEC) Pamekasan. By using qualitative methods, the narrative type is expected to find out more in-depth information about the application of sensory and motor methods. By using observation, interviews, and documents, it is expected to obtain to achieve the research objectives. In this study, it is found that students become more active by using motoric and sensory play methods, then it is also found that using motoric and sensory play methods can help students in mastering vocabulary, which students are more in mastering vocabulary in English. Thus, it is proven that applying motor and sensory play methods can make students more active and master more vocabulary in English language learning. The study has implications in developing English language learning methods, especially in vocabulary.